Vitamin D receptor gene polymorphisms and susceptibility of hand osteoarthritis in Finnish women - Solovieva, Svetlana (BioMed Central, 2006)
We examined whether polymorphisms of the vitamin D receptor (VDR) gene was associated with individual risk of hand osteoarthritis (OA). Radiographs of both hands of 295 dentists and of 248 teachers were examined and classified for the presence of OA using reference images. The VDR ApaI and TaqI genotypes were determined by PCR-based methods. No association was observed between the VDR polymorphisms and the odds of overall hand OA. However, the carriers of the VDR t allele or At haplotype were at almost half the odds of symmetrical hand OA (odds ratio [OR] = 0.60, 95% confidence interval [CI] = 0.38–0.94 and OR = 0.59, 95% CI = 0.38–0.93, respectively) compared with the carriers of the T allele and of the non-At haplotype, respectively. Increased odds of this disease, on the contrary, was observed for women with two copies of the VDR a allele (OR = 1.93, 95% CI = 1.99–3.70) compared with women with the AA genotype. Conversely, the VDR a allele carriage was associated with a tendency of lowered odds of osteophyte (OR = 0.51, 95% CI = 0.25–1.03). When the genotype data were used to construct haplotypes, the VDR AaTt joint genotype appeared to pose a remarkably lower odds (OR = 0.26, 95% CI = 0.08–0.91) of osteophyte compared with the AAtt joint genotype. As a novel finding we observed a joint effect of a low calcium intake and VDR polymorphisms on symmetrical OA; the OR was 2.64 (95% CI = 1.29–5.40) for carriers of the aT haplotype with low daily calcium intake compared with non-carriers of the haplotype with high daily calcium intake. Our results suggest that VDR gene polymorphisms play a role in the etiology of symmetrical hand OA. Moreover, the association between the VDR gene and OA may be modified by calcium intake.